Right ventricular stroke work correlates with outcomes in pediatric pulmonary arterial hypertension - Yang, Weiguang (Pulm Circ, 2018)
Pulmonary arterial hypertension (PAH) is characterized by elevated pulmonary artery pressures (PAP) and pulmonary vascular resistance (PVR). Optimizing treatment strategies and timing for transplant remains challenging. Thus, a quantitative measure to predict disease progression would be greatly beneficial in treatment planning. We devised a novel method to assess right ventricular (RV) stroke work (RVSW) as a potential biomarker of the failing heart that correlates with clinical worsening. Pediatric patients with idiopathic PAH or PAH secondary to congenital heart disease who had serial, temporally matched cardiac catheterization and magnetic resonance imaging (MRI) data were included. RV and PA hemodynamics were numerically determined by using a lumped parameter (circuit analogy) model to create pressure-volume (P-V) loops. The model was tuned using optimization techniques to match MRI and catheterization derived RV volumes and pressures for each time point. RVSW was calculated from the corresponding P-V loop and indexed by ejection fraction and body surface area (RVSW(EF)) to compare across patients. Seventeen patients (8 boys; median age = 9.4 years; age range = 4.4–16.3 years) were enrolled. Nine were clinically stable; the others had clinical worsening between the time of their initial matched studies and their most recent follow-up (mean time = 3.9 years; range = 1.1–8.0 years). RVSW(EF) and the ratio of pulmonary to systemic resistance (Rp:Rs) values were found to have more significant associations with clinical worsening within one, two, and five years following the measurements, when compared with PVR index (PVRI). A receiver operating characteristic analysis showed RVSW(EF) outperforms PVRI, Rp:Rs and ejection fraction for predicting clinical worsening. RVSW(EF) correlates with clinical worsening in pediatric PAH, shows promising results towards predicting adverse outcomes, and may serve as an indicator of future clinical worsening.